Ischemic left ventricle systolic dysfunction: An evidence-based approach in diagnostic tools and therapeutics - Lima,Eduardo Gomes (2017)
Summary Coronary artery disease (CAD) associated with left ventricular systolic dysfunction is a condition related to poor prognosis. There is a lack of robust evidence in many aspects related to this condition, from definition to treatment. Ischemic cardiomyopathy is a spectrum ranging from stunned myocardium associated with myocardial fibrosis to hibernating myocardium and repetitive episodes of ischemia. In clinical practice, relevance lies in identifying the myocardium that has the ability to recover its contractile reserve after revascularization. Methods to evaluate cellular integrity tend to have higher sensitivity, while the ones assessing contractile reserve have greater specificity, since a larger mass of viable myocytes is required in order to generate contractility change. Since there are many methods and different ways to detect viability, sensitivity and specificity vary widely. Dobutamine-cardiac magnetic resonance with late gadolinium enhancement has the best accuracy is this setting, giving important predictors of prognostic and revascularization benefit such as scar burden, contractile reserve and end-systolic volume index. The latter has shown differential benefit with revascularization in some recent trials. Finally, authors discuss interventional procedures in this population, focusing on coronary artery bypass grafting and evolution of evidence from CASS to post-STICH era.